Impact of the social and health crisis on live music: music intermediaries facing long-standing issues of artistic work in Chile (Revista Argentina de Musicología, 2022)
Live music is one of the most profitable sectors for the music industry in the 21st century. With fluctuations, it has managed to generate collaborative relations into the musical ecosystem. In Chile, the live music industry experienced two crises: the social movement of October 2019, and the arrival of the pandemic in March 2020, which meant the cancellation of the scheduled live events during the high season, historically concentrated in the summer. In this context, I argue that the double crisis (social and health) made an old problem in the sector visible: as it is not considered by public institutions, it has often been excluded from support and instances of dialogue due to the lack of clarity about the particularity of its role in the industry. As a consequence, different organizations of musical intermediaries reactivated their networks of labor organizations, or created new ones, to generate strategies corresponding to the work they do, in order to overcome the labor crisis and to project the continuity of the live music industry in a post-pandemic future.
Keywords: live music; music intermediaries; industry; labor organization; musical work